2020
DOI: 10.3389/fbioe.2020.00573
|View full text |Cite
|
Sign up to set email alerts
|

Reversible pH Responsive Bovine Serum Albumin Hydrogel Sponge Nanolayer

Abstract: A pH dependent reversible sponge like behavior of a bovine serum albumin (BSA) nanolayer adsorbed at the gold-saline interface is revealed by quartz crystal microbalance with dissipation (QCM-D), atomic force microscope (AFM) and contact angle measurements. During the saline rinsing cycles, the BSA layer adsorbs water molecules at pH 7.0 and releases them at pH 4.5. The phenomenon remains constant and reproducible upon multiple rinsing cycles. The BSA layer thickness also increases upon rinsing with saline at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 36 publications
2
28
0
Order By: Relevance
“…The carrier protein BSA was encapsulated within all nanoparticle formulations where a 40−65% encapsulation efficiency was achieved, as determined with a BCA protein assay (Figure S2A). In addition, we found that BSA, which is negatively charged at physiological pH, 38 contributed moderately to the negative charge of the nanoparticles when encapsulated therein (Figure S2B). As we decreased the molecular weight of PLGA, the zeta potential of the nanoparticles became more negative.…”
Section: ■ Results and Discussionmentioning
confidence: 95%
“…The carrier protein BSA was encapsulated within all nanoparticle formulations where a 40−65% encapsulation efficiency was achieved, as determined with a BCA protein assay (Figure S2A). In addition, we found that BSA, which is negatively charged at physiological pH, 38 contributed moderately to the negative charge of the nanoparticles when encapsulated therein (Figure S2B). As we decreased the molecular weight of PLGA, the zeta potential of the nanoparticles became more negative.…”
Section: ■ Results and Discussionmentioning
confidence: 95%
“…When analyzing the conductivity characteristics of the considered solution, we may conclude that it is a strong electrolyte. It follows from the pH value of BSA (4.5–4.8) [ 21 ] that was primarily added when obtaining the CLEA. Hence, we can use Kohlrausch’s law for a solution of a strong electrolyte: …”
Section: Resultsmentioning
confidence: 99%
“…As a model protein, BSA has an isoelectric point (IEP) of 4.5-4.8 which means under neutral pH condition, it has a negative molecular net charge. 50 However, PDGF has an IEP of 9.8 and turns to have a positive molecular net charge under the physiological milieu. 51 As the CS bioadhesives are positively charged from the amine groups, it is predictable that PDGF will have a faster-releasing profile compared to BSA due to the electrostatic force of repulsion which is beneficial to maintain a therapeutic concentration level within the dynamic homeostasis environment.…”
Section: Discussionmentioning
confidence: 99%